Effects of route of administration of a commercially available Mannheimia (pasteurella) haemolytica vaccine on titer levels - Marston, T.T.; Llewellyn, Donald A.; Stokka, Gerald L.; Hollis, Larry C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred thirteen Hereford x Angus heifer calves (average weight = 515 lb) were allotted to one of three treatments: 1) control, no vaccine; 2) a 2-cc subcutaneous injection of One-Shot® (Pfizer Animal Health), a Mannheimia (pasteurella) haemolytica vaccine, three weeks before weaning; or 3) a ½-cc intradermal injection of One-Shot, three weeks before weaning. All heifers were weighed and blood samples harvested at time of injection, three weeks later at weaning, and then 28 days later. After weaning, heifers were confined to a common pen and fed free-choice brome hay and approximately 5 lb/head daily of a concentrate. Blood samples from 30 heifers were shipped to a laboratory for titer analysis. No differences were found in animal performance and sickness during the preconditioning period. Heifers injected by the subcutaneous route had greater increases in whole-cell and leukotoxin-neutralizing antibody titer levels than the intradermal or control treatments. These data suggest that beef producers should follow label recommendations for dosage and route of administration to maximize vaccine efficacy.
Keywords: Beef; Mannheimia (pasteurella) haemolytica vaccine; Titer levels